PENGGUNAAN METODE NILAI HASIL (EARNED VALUE ANALYSIS) TERHADAP BIAYA DAN WAKTU PADA PROYEK KONSTRUKSI BANGUNAN PERUMAHAN (STUDI KASUS PROYEK KONSTRUKSI BANGUNAN PERUMAHAN PT. GRAHA PRAJA KENCANA DI DESA CEGUK KECAMATAN TLANAKAN KABUPATEN PAMEKASAN) - Asmaroni, Dedy; Setiawan, Aldi (Universitas Dr. Soetomo, 2020)
In a construction project there are various stages related to construction management, in which there are various problems regarding the management of costs and time off work so that in its implementation we need a system for cost management and time management so that in its implementation, the project can be completed on time as planned and the costs incurred according to the needs of the project being worked on. In writing this article the main study is, how is the project performance in terms of cost and time, how is the application of EVA (Earned Value Analysis) to predict the costs and the final time of completion of the project, are there any advantages or disadvantages that may occur in the completion of a construction project PT Graha Praja Kencana Residential Building in Ceguk Village, Tlanakan District, Pamekasan Regency? To answer this problem, a qualitative approach with a descriptive type was conducted. Sources of data obtained through interviews, observations, and documentation with respondents, namely consultants, contractors, and the Director of PT Graha Praja Kencana. From the results of data analysis, it can be concluded that shows that the costs incurred are lower than the planned budget, the time of project implementation according to the schedule from the initial planning, the costs incurred every week from week 1 to week 9 experienced a very significant increase, and the profits obtained by the contractor until the end of the project starting from the first week to the 9th week of Rp. Rp. 8,978,737.20.